Barriers to ICT use in EFL teacher education courses in Nepal: An activity theory perspective - Laudari, Suman; Maher, Damian (Journal of NELTA, 2019)
The effectiveness of pre-service teachers’ ICT training during teacher education course is often linked with the teacher educators’ (TEs’) practices. TEs’ digital practices, however, are under-studied, thus, are not fully understood. This study, which draws on the theoretical tenets of Activity Theory, reports on the factors that limit TEs’ digital practices in a context where technology use has just begun to evolve. Using a multi-method case study, this study collected data from EFL TEs and policymakers. The analyses of the policy data and interviews reveal that multiple factors constrain TEs’ digital practices. A key finding of the study is that factors related to ICT policies, training for TEs and resources hindered the use of technology by TEs. Implications of these are discussed.